Traditional Therapeutic Uses of Plants of Asteraceae from Semi-Arid Regions of Barmer, Rajasthan, India - Vimala; Hans, Dinesh (Indian Forester, 2024)
Documentation of traditional therapeutic uses is very important in contemporary situation. It also helps to reuse the local plants against the health problems, raise awareness among locals and conservation of locally available plants of a landscape. Keeping this in mind, a attempt has been made to document the ethnomedicinal practices under ITK of plants belonging to Asteraceae family of Barmer, Rajasthan, India. Largest species of the family is rational behind the selection. A survey was made in 2022-2023 and collected information through PDF (passport data form) and voucher numbers of enumerated plants are maintained. The results revealed that about 10 species are commonly used to treat various health problems belonging to 8 tribe. The morphological characters, habit, habitat along with uses are presented here. The communication bring attention towards documentation and uses of locally available ethnomedicinal plants of the state.Â